Políticas educacionais do campo: Pronera e Procampo no Maranhão - Menezes, Marly Cutrim de (2013)
The present PhD work is a study on educational policies in the countryside of the State of Maranhão, highlighting the materiality of education in the countryside in different instances of civil society and the conquest of their space in society. The educational policy, developed universally and implemented by constructing an educational policy for the countryside, combines the universality and specialty of the right to educate, seeking new pedagogical practices. It establishes a counterpoint between rural education and education in the countryside, and analyzes two programs that address higher education: the National Program of Education and Land Reform (Pronera-Programa Nacional de Educação e Reforma Agrária) and the Program of Support to Higher Education in Countryside Teaching (Procampo- Programa de Apoio à Formação Superior em Licenciatura do Campo). It investigates the training and pedagogical practices of countryside teachers at the level of higher education from the perspective of building a new project of education. In the teachinglearning process the methodology of Alternance is the basis of education. It contributes to a political-pedagogical change at countryside schools, considering that the rise of this new social practice was a response to the right of countryside populations to have the political-pedagogical experiences accumulated by these subjects acknowledged and legitimized by the public system in the appropriate spheres. Joint concern about the training and performance of countryside teachers within the scope of Higher Education is also necessary to improve basic education